2011
DOI: 10.1177/107769901108800108
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Comparison of Two Perspectives on the Concept of Need for Orientation in Agenda-Setting Theory

Abstract: Need for orientation (NFO) is a key contingent condition for agenda-setting effects. Traditionally, this concept has been measured by two lower-order components, but a recent reconceptualization expanded it to three dimensions. The current experimental study tested how comparable the traditional and new NFO scales are, and how strongly they predict agenda setting. Findings indicate that both NFO scales are (1) reliable tools for predicting first-level agenda-setting effects, and (2) significantly correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 2 publications
0
23
0
1
Order By: Relevance
“…This is an important finding in itself because the exploration of the link between values and agenda setting is at the initial stage. These results open another venue for investigating the role of psychological determinants of the agendasetting process, in a similar vein as previous studies that demonstrated the impact of motivations, such as need for orientation (Chernov, Valenzuela, & McCombs, 2011), and attitudes (Kiousis & McCombs, 2004). Furthermore, replications of existing studies are called highly desirable both in the broader field of communication (Benoit & Holbert, 2008) and agenda-setting theory itself (McCombs, 2004 Stroud (2010) demonstrated that partisan media deepens audience polarization on the issues that involve deeply ingrained beliefs and values.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…This is an important finding in itself because the exploration of the link between values and agenda setting is at the initial stage. These results open another venue for investigating the role of psychological determinants of the agendasetting process, in a similar vein as previous studies that demonstrated the impact of motivations, such as need for orientation (Chernov, Valenzuela, & McCombs, 2011), and attitudes (Kiousis & McCombs, 2004). Furthermore, replications of existing studies are called highly desirable both in the broader field of communication (Benoit & Holbert, 2008) and agenda-setting theory itself (McCombs, 2004 Stroud (2010) demonstrated that partisan media deepens audience polarization on the issues that involve deeply ingrained beliefs and values.…”
Section: Discussionmentioning
confidence: 48%
“…As Chernov, Valenzuela, and McCombs (2011) noted, NFO describes "individual differences in the desire for orienting cues and information [and] explains differences in attention to the media agenda and, consequently, differences in the degree to which individuals accept the media agenda" (p. 143). The key subdomains of NFO-uncertainty and relevance-allow for a finer distinction of the values-issue salience relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Matthes (2008) found that NFO leads to the increase of the perceived media salience of the issue of unemployment. Chernov, Valenzuela, and McCombs (2011) found that this NFO measure predicted the agenda-setting effects on the issue of drug abuse.…”
Section: The Need For Orientation Conceptmentioning
confidence: 96%
“…The operationalization of the NFO in the present study is also guided by the research of Chernov et al (2011), which compared the old measurement of the NFO with the new one suggested by Matthes (2006). That study found that the traditional measurement was a better predictor of agendasetting effects than the new multidimensional NFO scale.…”
Section: The Need For Orientation Conceptmentioning
confidence: 96%
“…As a result, the high need for orientation leads to more attention to messages in the media, thereby increasing the effect of the first-level agenda-setting. However, with regard to the attention given to certain characteristics of events or public figures (Camaj and Weaver 2013;Chernov, Valenzuela, and McCombs 2011).…”
Section: Agenda-setting Theorymentioning
confidence: 99%